Impact of Financial Ratios on Profitability of Commercial Banks in Nepal - Khanal, Kapil (Journal of Contemporary Review, 2024)
The purpose of the study was to understand the impact of some financial ratios on the profitability of commercial banks in Nepal. Secondary data were collected through annual reports and publications of thirty commercial banks. Multiple regression models were used to analyze and interpret the data. Analysis showed that the amount of impact of the financial ratios on bank’s profitability varies from bank to bank in Nepal.